Effects of methadone on the minimum alveolar concentration of isoflurane in dogs - Credie, Renato G. [UNESP]; Teixeira Neto, Francisco José [UNESP]; Ferreira, Tatiana H. [UNESP]; Aguiar, Antonio J. A. [UNESP]; Restitutti, Fabio C.; Corrente, Jose E. [UNESP] (Wiley-Blackwell, 2010)
Objective To investigate the effects of methadone on the minimum alveolar concentration of isoflurane (ISO(MAC)) in dogs.Study design Prospective, randomized cross-over experimental study.Animals Six adult mongrel dogs, four males and two females, weighing 22.8 +/- 6.6 kg.Methods Animals were anesthetized with isoflurane and mechanically ventilated on three separate days, at least 1 week apart. Core temperature was maintained between 37.5 and 38.5 degrees C during ISO(MAC) determinations. on each study day, ISO(MAC) was determined using electrical stimulation of the antebrachium (50 V, 50 Hz, 10 mseconds) at 2.5 and 5 hours after intravenous injection of physiological saline (control) or one of two doses of methadone (0.5 or 1.0 mg kg(-1)).Results Mean (+/- SD) ISO(MAC) in the control treatment was 1.19 +/- 0.15% and 1.18 +/- 0.15% at 2.5 and 5 hours, respectively. The 1.0 mg kg(-1) dose of methadone reduced ISO(MAC) by 48% (2.5 hours) and by 30% (5 hours), whereas the 0.5 mg kg(-1) dose caused smaller reductions in ISO(MAC) (35% and 15% reductions at 2.5 and 5 hours, respectively). Both doses of methadone decreased heart rate (HR), but the 1.0 mg kg(-1) dose was associated with greater negative chronotropic actions (HR 37% lower than control) and mild metabolic acidosis at 2.5 hours. Mean arterial pressure increased in the MET1.0 treatment (13% higher than control) at 2.5 hours.Conclusions and clinical relevance Methadone reduces ISO(MAC) in a dose-related fashion and this effect is lessened over time. Although the isoflurane sparing effect of the 0.5 mg kg(-1) dose of methadone was smaller in comparison to the 1.0 mg kg(-1) dose, the lower dose is recommended for clinical use because it results in less evidence of cardiovascular impairment.
Keywords: isoflurane; methadone; minimum alveolar concentration